Near-infrared spectroscopy (NIRS) in vivo assessment of skeletal muscle oxidative capacity: a comparison of results from short versus long exercise protocols and reproducibility in non-athletic adults - Tandirerung, Fistra J.; Jamieson, Alexandra; Hendrick, Elizabeth; Hughes, Alun D.; Jones, Siana (Frontiers in Physiology, 2024)
Background. Near-infrared spectroscopy (NIRS) provides a non-invasive, cost-effective method for assessing skeletal muscle oxidative capacity when combined with a short exercise protocol and arterial occlusions. However, the impact of different exercise protocols and reproducibility of the method in non-athletic adults have not previously been assessed.Methods. Young, non-athletic adults (YA) were invited to perform a short duration, fast frequency contraction (SF) exercise protocol and a long duration slow frequency (LS) contraction protocol, combined with NIRS measurements and arterial occlusions to assess skeletal muscle oxidative capacity. YA and older non-athletic adults (OA; >65 years old) were invited to perform the SF exercise protocol twice to assess the reproducibility of this oxidative capacity measurement.Results. We included 25 participants (14 male (56%), age range: 18-86 years) in the analyses. There was a strong positive correlation and good agreement between time constants derived following the SF and LS exercise protocols (Lin's concordance correlation coefficient: 0.69, pvalue <0.001 mean bias [LoA]: -3.2 [-31.0, 24.4] seconds. There was a strong positive correlation and good agreement between time constants derived from the SF exercise protocol in the YA & OA group (Lin's concordance correlation coefficient: 0.63, p-value <0.001; mean bias [LoA] -6.4 [-34.0.96, 21.3]).These data provide evidence to suggest that NIRS is a reliable in vivo method for the assessment of skeletal muscle oxidative capacity irrespective of exercise protocol duration or muscle contraction frequency. NIRS-measured oxidative capacity via the SF exercise protocol was reproducible in non-athletic adults with a wide range in age.